Autoantibodies Against Perilipin 1 as a Cause of Acquired Generalized Lipodystrophy - Corvillo, Fernando; Aparicio, Verónica; López-Lera, Alberto; Garrido, Sofía; Araújo-Vilar, David; de Miguel, María P.; López-Trascasa, Margarita (Frontiers in Immunology, 2018)
Acquired generalized lipodystrophy (AGL) is a rare condition characterized by an altered distribution of adipose tissue and predisposition to develop hepatic steatosis and fibrosis, diabetes, and hypertriglyceridemia. Diagnosis of AGL is based on the observation of generalized fat loss, autoimmunity and lack of family history of lipodystrophy. The pathogenic mechanism of fat destruction remains unknown but evidences suggest an autoimmune origin. Anti-adipocyte antibodies have been previously reported in patients with AGL, although their involvement in the pathogenesis has been poorly studied and the autoantibody target/s remain/s to be identified. Using a combination of immunochemical and cellular studies, we investigated the presence of anti-adipocyte autoantibodies in patients with AGL, acquired partial lipodystrophy, localized lipoatrophy due to intradermic insulin injections or systemic lupus erythematosus. Moreover, the impact of anti-adipocyte autoantibodies from AGL patients was assessed in cultured mouse preadipocytes. Following this approach, we identified anti-perilipin 1 IgG autoantibodies in the serum of patients with autoimmune variety-AGL, but in no other lipodystrophies tested. These autoantibodies altered the ability of perilipin 1 to regulate lipolysis in cultured preadipocytes causing abnormal, significantly elevated basal lipolysis. Our data provide strong support for the conclusion that perilipin 1 autoantibodies are a cause of generalized lipodystrophy in these patients.